Re-evaluating ambiguous age relationships in Archean cratons: implications for the origin of ultramafic-mafic complexes in the Lewisian Gneiss Complex - Guice, G; McDonald, I; Hughes, HSR; MacDonald, J; Blenkinsop, T; Goodenough, K; Faithfull, J; Gooday, R (Precambrian Research, 2018)
This is the author accepted manuscript. The final version is available from the publisher via the DOI in this record. Archean ultramafic-mafic complexes have been the focus of important and often contentious geological and geodynamic interpretations. However, their age relative to the other components of Archean cratons are often poorly-constrained, introducing significant ambiguity when interpreting their origin and geodynamic significance. The Lewisian Gneiss Complex (LGC) of the northwest Scottish mainland – a high-grade, tonalite-trondhjemite-granodiorite (TTG) terrane that forms part of the North Atlantic Craton (NAC) – contains a number of ultramafic-mafic complexes whose origin and geodynamic significance have remained enigmatic since they were first described. Previous studies have interpreted these complexes as representing a wide-range of geological environments, from oceanic crust, to the sagducted remnants of Archean greenstone belts. These interpretations, which are often critically dependent upon the ages of the complexes relative to the surrounding rocks, have disparate implications for Archean geodynamic regimes (in the NAC and globally). Most previous authors have inferred that the ultramafic-mafic complexes of the LGC pre-date the TTG magmas. This fundamental age relationship is re-evaluated in this investigation through re-mapping of the Geodh’ nan Sgadan Complex (where tonalitic gneiss reportedly cross-cuts mafic rocks) and new mapping of the 7 km2 Ben Strome Complex (the largest ultramafic-mafic complex in the LGC), alongside detailed petrography and spinel mineral chemistry. This new study reveals that, despite their close proximity in the LGC (12 km), the Ben Strome and Geodh’ nan Sgadan Complexes are petrogenetically unrelated, indicating that the LGC (and thus NAC) records multiple temporally and/or petrogenetically distinct phases of ultramafic-mafic Archean magmatism that has been masked by subsequent high-grade metamorphism. Moreover, field observations and spinel mineral chemistry ...